Analysis of the Main Characters in Film Titanic by James Cameron - Imakulata Suryani Danda; Ni Nyoman Deni Ariyaningsih (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2024)
This study is mainly focus on to find out the types of characters and the characterizations of the main character in the film entitle “Titanic” by James Cameron. The study used two theories. The first theory is developed by Kenney ( 1998) that is used in analyzing the types of main character and the second theory from Wellek and Warren (1976) which is used in analyzing the characterization of the main character. The data were qualitatively analyzed and presented descriptively based on the theories adopted. Protagonist character was found as the finding result of the study the type of the character classified as major and dynamic character. In showing the type of the character and characterization of main character,the analysis used picture or scenes and the dialogue from the film. There are three aspects of characterization of all main characters that were found. Those are physiological, psychological and sociological aspects.